The Influence of the Guided Inquiry Learning Model on the Material of Work and Energy on Science Process Skills at MTsS Balimbing - Chandra, Artha Nesa; Rahmiati, Silvi; Fajar, Najmiatul; Imamora, Marjoni (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2025)
The purpose of this study was to see the effect of guided inquiry learning model on students' science process skills on work and energy. The type of research is Quasi Experimental research and the research design used is Posttest Only Control Group Design. The sample consists of 2 classes, the experimental class is class VIII 1 and the control class is class VIII 2 consisting of 37 students. The sampling technique used is simple random sampling. The instrument used in the study was a final test of 20 questions. The results of the science process skills data analysis showed an average score of science process skills test of 70.43%, while students in the control class obtained an average score of science process skills test of 60.53%. The results of the data test were analyzed using the t-test formula, which showed that t (count) > t (table) was 2.98 > 2.02. This shows that the use of guided inquiry learning model on work and energy material has an effect on the science process skills of class VIII students at MTsS Balimbing.